DNA Computing for Subgraph Isomorphism Problem and Related Problems - Hsieh, Sun‐Yuan; Huang, Chao‐Wen; Chou, Hsin‐Hung (Algorithms in Computational Molecular Biology: Techniques, Approaches and Applications, 2011)
This chapter contains sections titled: Introduction Definitions of Subgraph Isomorphism Problem and Related Problems DNA Computing Models The Sticker‐based Solution Space Algorithms for Solving Problems Experimental Data Conclusion References